If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-2(0)-6y=6
We simplify the equation to the form, which is simple to understand
-2(0)-6y=6
Reorder the terms in parentheses
+(-0)-6y=6
Remove unnecessary parentheses
-0-6y=+6
We move all terms containing y to the left and all other terms to the right.
-6y=+6
We simplify left and right side of the equation.
-6y=+6
We divide both sides of the equation by -6 to get y.
y=-1
| (x+2y)(2x+3y)= | | x^2=-6 | | 7-10n+5n=22-90 | | (-x-4)(4+3x)= | | 3-2=1 | | 4x^2=8x+5 | | 4(c-5)+9=6+c-17 | | 4y=8x-12 | | v^2x^2-9x^2+v^2n^2-9n^2=0 | | 5a-8.7=2.6a-2.22 | | 3(0)-4y=24 | | 2a+1.8=4.3a-14.99 | | 3x-4(0)=24 | | (2x+5)(4x-3)= | | 2b(7)=11 | | (4x-9)(3x+1)= | | 0=3x-9 | | 8m+16=0 | | (3x+2)(2x+5)= | | -4x-2(0)=8 | | graphy=-4a^2+2a+2 | | s=116t-1+16t | | A+(B+C)=(A+B)+C | | -3(t+5)=0 | | r=0.2 | | 9(w-2)=18 | | -2y-9=8y+21 | | -6x-7=17 | | s(t)=16t^2+96+20 | | 22+44=44 | | 14=-3x+17 | | 34xm-5x=0 |